The Influence of Organizational Commitment on Teacher’s Organizational Citizenship Behavior (OCB) at Islamic Education Institution - M. Yusuf Alfian Rendra Anggoro KR; Rachma Yuliana; Putu Agus Eka Rismawan; Ilham Ilham; Sukirman Sukirman (Journal on Education, 2023)
This study's objective is to show how organizational commitment to organizational citizenship behavior (OCB) among teachers in academic institutions. A quantitative methodology is used in this research, employing the causal relationship research method, with path analysis in answering the hypothesis. A questionnaire and a documentation study were used to gather the data, and a sample of 42 teachers was chosen using a simple random sampling approach. Based on the data processing and calculation results of SPSS Version 22, statistical testing resulted in Ho being rejected and Ha being accepted, it shows that in educational institutions, organizational commitment has a 0.727 influence on instructors' organizational citizenship behavior (OCB). The results of the t-test, which had a significance level of 0.000 5% and a t-count of 6.689 > t-table, or 2.021 (0.05). As a result, the hypothesis also establishes that organizational commitment has a considerable impact on teachers' organizational citizenship behavior (OCB) in educational institutions. According to the computation of the coefficient of determination, the organizational commitment variable accounts for 52.8% of the organizational citizenship behavior (OCB) variable. Variables not examined account for the remaining 47.2% of the variance.